Respuesta :
-(-1)+4=-1+6
1+4=-1+6
5=5
I hope that helped there’s the step by step to explain a little more that first x was already a negative so so to plug it in you would have to bring that negative in ground of the answer of x like so -(-1) those negative would then cancel each other out making it just 1 but if x=1 then it would be -(1) and it was make it -1 hope this helped :)
1+4=-1+6
5=5
I hope that helped there’s the step by step to explain a little more that first x was already a negative so so to plug it in you would have to bring that negative in ground of the answer of x like so -(-1) those negative would then cancel each other out making it just 1 but if x=1 then it would be -(1) and it was make it -1 hope this helped :)